Development of a patient-reported outcome questionnaire for use in adults with moderate-to-severe plaque psoriasis: The Psoriasis Symptoms and Signs Diary - Steven R. Feldman; Susan D. Mathias; Brad Schenkel; Hilary H. Colwell; Kelly McQuarrie; Bruce Randazzo; Chenglong Han (Wolters Kluwer Medknow Publications, 2016)
Background: Patients with psoriasis (PsO) suffer from a variety of symptoms. Tools are needed to assess PsO symptoms and signs from the patient's perspective. Objective: To develop a patient-reported outcome (PRO) measure to assess symptoms and signs in individuals with moderate-to-severe PsO. Methods: Face-to-face concept elicitation interviews were conducted with 20 subjects with moderate-to-severe plaque PsO. Results from the interviews, a literature review, and clinical input informed the development of the draft Psoriasis Symptoms and Signs Diary (PSSD). Three waves of face-to-face cognitive interviews (n = 19) were conducted to evaluate the clarity and relevance of the PSSD. Additional interviews (n = 5) were conducted to confirm its content. Results: The PSSD assesses severity of 5 symptoms (itch, pain, stinging, burning, skin tightness) and 6 observable signs (skin dryness, cracking, scaling, shedding or flaking, redness, bleeding) using 0-10 numerical ratings. Two versions with different recall periods (24 h and past 7 days) were developed. PsO patients found the PSSD to be clear and relevant. Limitations: The sample had limited racial diversity. Conclusion: The PSSD, developed according to the Food and Drug Administration PRO Guidance, assesses severity of symptoms and signs commonly associated with plaque PsO. Its measurement properties are currently being evaluated.